Diagnostic test accuracy of ultrasound for sarcopenia diagnosis: A systematic review and meta‐analysis. Issue 1 (13th December 2022) - Fu, Hongbo; Wang, Lei; Zhang, Wenyi; Lu, Jing; Yang, Ming
Abstract: Muscle ultrasound is an emerging tool for diagnosing sarcopenia. This review aims to summarize the current knowledge on the diagnostic test accuracy of ultrasound for the diagnosis of sarcopenia. We collected data from Ovid Medline, Embase and the Cochrane Central Register of Controlled Trials. Diagnostic test accuracy studies using muscle ultrasound to detect sarcopenia were included. Bivariate random‐effects models based on sensitivity and specificity pairs were used to calculate the pooled estimates of sensitivity, specificity and the area under the curves (AUCs) of summary receiver operating characteristic (SROC), if possible. We screened 7332 publications and included 17 studies with 2143 participants (mean age range: 52.6–82.8 years). All included studies had a high risk of bias. The study populations, reference standards and ultrasound measurement methods varied across the studies. Lower extremity muscles were commonly studied, whereas muscle thickness (MT) was the most widely measured parameter, followed by the cross‐sectional area (CSA). The MTs of the gastrocnemius, rectus femoris, tibialis anterior, soleus, rectus abdominis and geniohyoid muscles showed a moderate diagnostic accuracy for sarcopenia (SROC‐AUC 0.83, 8 studies; SROC‐AUC 0.78, 5 studies; AUC 0.82, 1 study; AUC 0.76–0.78, 2 studies; AUC 0.76, 1 study; and AUC 0.79, 1 study, respectively), whereas the MTs of vastus intermedius, quadriceps femoris and transversus abdominis muscles showed a low diagnostic accuracy (AUC 0.67–0.71, 3 studies; SROC‐AUC 0.64, 4 studies; and AUC 0.68, 1 study, respectively). The CSA of rectus femoris, biceps brachii muscles and gastrocnemius fascicle length also showed a moderate diagnostic accuracy (AUC 0.70–0.90, 3 studies; 0.81, 1 study; and 0.78–0.80, 1 study, respectively), whereas the echo intensity (EI) of rectus femoris, vastus intermedius, quadriceps femoris and biceps brachii muscles showed a low diagnostic accuracy (AUC 0.52–0.67, 2 studies; 0.48–0.50, 1 study; 0.43–0.49, 1 study; and 0.69, 1 study, respectively). The combination of CSA and EI of biceps brachii or rectus femoris muscles was better than either CSA or EI alone for diagnosing sarcopenia. Muscle ultrasound shows a low‐to‐moderate diagnostic test accuracy for sarcopenia diagnosis depending on different ultrasound parameters, measured muscles, reference standards and study populations. The combination of muscle quality indicators (e.g., EI) and muscle quantity indicators (e.g., MT) might provide better diagnostic test accuracy.